Isolated Double Aortic Arch (DAA) - prenatal detection with postnatal follow-up, case report and literature review - Murlewska, Julia; Żalińska, Agnieszka; Roik, Danuta; Werner, Bożena; Respondek-Liberska, Maria (Prenatal Cardiology, 2018)
This case report presents a prenatal diagnosis with postnatal confirmation (by angio CT and computer reconstruction) of an isolated double aortic arch, with no blood disturbances and with no clinical symptoms after birth. Literature review was focusing on the possible symptoms in the future. Prenatal findings should be forwarded to neonatologist and pediatrician despite clinical silence.